2020
DOI: 10.1038/s41586-020-2317-6
|View full text |Cite
|
Sign up to set email alerts
|

Structures of α-synuclein filaments from multiple system atrophy

Abstract: Synucleinopathies are human neurodegenerative diseases that include multiple system atrophy (MSA), Parkinson's disease, Parkinson's disease dementia (PDD) and dementia with Lewy bodies (DLB) (1). Existing treatments are at best symptomatic. These diseases are characterised by the presence in brain cells of filamentous inclusions of αsynuclein, the formation of which is believed to cause disease (2,3). However, the structures of α-synuclein filaments from human brain are not known. Here we show, using electron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
601
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 552 publications
(644 citation statements)
references
References 78 publications
39
601
3
1
Order By: Relevance
“…The N-terminal interaction hotspot on the monomer contains several lysine residues, which may be attracted to the highly negatively charged Cterminus of the oligomer. Conversely, αS amyloid fibrils possess both exposed disordered N-and C-termini flanking a rigid Greek-key fibril core, as observed in structural models determined by solid-state NMR and cryo-electron microscopy (18)(19)(20)(21)(22). In this way, αS fibrils also have a "fuzzy-coat" made of disordered C-termini (~residues 97-140) in addition to a "fuzzy-coat" made of disordered N-termini (~residues 1-36), providing the potential for αS monomers to interact with either the N-or C-termini of the fibrils (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The N-terminal interaction hotspot on the monomer contains several lysine residues, which may be attracted to the highly negatively charged Cterminus of the oligomer. Conversely, αS amyloid fibrils possess both exposed disordered N-and C-termini flanking a rigid Greek-key fibril core, as observed in structural models determined by solid-state NMR and cryo-electron microscopy (18)(19)(20)(21)(22). In this way, αS fibrils also have a "fuzzy-coat" made of disordered C-termini (~residues 97-140) in addition to a "fuzzy-coat" made of disordered N-termini (~residues 1-36), providing the potential for αS monomers to interact with either the N-or C-termini of the fibrils (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
“…Structural models derived from solid-state nuclear magnetic resonance (NMR) and cryo-electron microscopy (EM) have revealed that αS fibrils consist of two protofilaments with a rigid "Greek key" core flanked by intrinsically disordered N-and C-termini (~40 residues each) (18)(19)(20)(21)(22) (Figure 1a). These intrinsically disordered regions (IDRs) are a substantial fraction of the fibril structure and make up a "fuzzy coat" that surrounds the rigid core (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the mechanisms that initiate αS aggregation inside the cells are even more elusive, although particular, yet undefined, cellular microenvironments appear to be required for the accumulation of αS amyloid aggregates inside cells, as the sole overexpression of the protein seem to be unable to trigger the de novo nucleation of αS amyloid formation, and additional cellular insults are typically required 14 . Importantly, recent experimental evidences show that the αS amyloid structures that have been resolved at high resolution, in all cases generated in vitro by heterogeneous nucleation at the air/water interface [15][16][17][18] , differ remarkably from the amyloid structures obtained from patient brain extracts 19,20 , suggesting alternative in vivo amyloid pathways from those explored until now in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal α-synuclein is also a major component of glial cytoplasmic inclusions (GCIs), which are a pathological feature of multiple system atrophy (MSA), a neurodegenerative disease presenting with movement and autonomic disorders (Spillantini et al, 1998a; Wakabayashi et al, 1998a). In these disorders, referred to as α-synucleinopathies, ultrastructures of α-synuclein filaments containing β-pleated sheets (Serpell et al, 2000) may display diversity in disease-specific and individually variable manners as revealed by the latest cryo-electron microscopic analysis (Schweighauser et al, 2020). Previous studies experimentally demonstrated that α-synuclein fibrils acted as templates for the conversion of normal α-synuclein molecules into misfolded species, leading to the prion-like propagation of the α-synuclein fibrillogenesis throughout the brain via neural circuits (Luk et al, 2012a and 2012b; Masuda-Suzukake et al, 2013 and 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The tau PET ligand, 11 C-PBB3 was also documented to react with α-synuclein lesions, including Lewy bodies, Lewy neurites, and GCIs, while it has been indicated that its binding affinity for α-synuclein pathologies is not sufficient for sensitive PET detection of these lesions in living individuals (Koga et al, 2017; Perez-Soriano et al, 2017). Indeed, PBB3 shows high affinity and selectivity for the β-sheet structure of tau filaments, which is assumed to be ultrastructurally distinct from that of α-synuclein assemblies (Ono et al, 2017; Fitzpatrick et al, 2017; Goedert et al, 2018; Falcon et al, 2018; Guerrero-Ferreira et al, 2018 and 2019; Schweighauser et al, 2020). In the meantime, the modest reactivity of PBB3 with α-synuclein inclusions implies its utility as a starting material for the development of novel derivatives with more appropriate binding properties for in vivo imaging of α-synucleinopathies.…”
Section: Introductionmentioning
confidence: 99%